THE EFFECTIVENESS OF TRAINING THROWING SHOT PUT USING TWO EXPERIMENTAL METHODS OF TRAINING – TRAINING AND TRADITIONAL, STUDENTS OF PHYSICAL EDUCATION AT THE UNIVERSITY OF YARMOUK, JORDAN - Makhadmeh, Abd - Alkhareem (Scientific Journal Management in Sports, 2014)
The aim of this study is to determine the effectiveness of two methods of shot put teaching: traditional and training, with students of athletics at the Faculty of Physical Education and the effects of these techniques on the overall results in throwing shot put and the development of some physical properties. Two groups of students of the Faculty of Physical Education were involved (20 students). Each group consisted of 10 students. The results showed that there were significant statistical differences between the two measurements before and after the experiment in each group, showing physical development of abilities and the results of throw- ing shot put. After the experiment, between two groups of indicators were noticed differences.